Landfills as risk factors for respiratory disease in children - Silveira Correa, Carlos Roberto; Cantusio Abrahao, Carlos Eduardo; Cabral Carpintero, Maria do Carmo; Anaruma Filho, Francisco [UNESP] (Sociedade Brasileira de Pediatria, 2011)
Objective: To investigate the relationship between exposure to a landfill site closed 6 years previously and respiratory symptoms in children aged up to 13 years.Method: This was a cross-sectional study conducted in Varzea Paulista, in the state of São Paulo, Brazil. One adult in every household in a neighborhood close to the landfill and from a randomized sample of households in another neighborhood with similar socioeconomic characteristics but no landfill were interviewed and asked about respiratory symptoms and other variables relating to children aged up to 13. A logistic regression model was used to study this relationship.Results: The likelihood of a child having respiratory symptoms was a function of -2.36 + 0.43 if the child was less than 2 years old; + 0.24 if the child lived in the landfill area; -0.67 if there was a computer at home; + 0.54 if firewood was burnt in the home in the last year; + 0.94 if the child was diagnosed with asthma; + 0.87 if the child visited a health service in the previous 30 days.Conclusion: The authors conclude that living near to a landfill closed 6 years previously may be a risk factor for respiratory disease in children.